Is property management viewed as a value-added service?. Issue 2 (15th April 2019) - Read, Dustin C.; Carswell, Andrew
Abstract : Purpose: The purpose of this paper is to examine the perspectives of real estate executives to assess the extent to which property management is viewed as a commodity or as a value-added professional service contributing positively to investment performance and property value maximization. Design/methodology/approach: The qualitative analysis draws on the result of 93 semi-structured interviews conducted with executives employed by some of the largest real estate investment management and service firms across the USA. Findings: The findings suggest that significant perceptual cleavages exist in the real estate industry, with some executives believing property managers are incredibly important to the value creation process and others believing they play a much more modest role. Practical implications: The results highlight the need for the property management industry as whole to continue its efforts to gain recognition as a value-added professional service and for individual property management companies to actively take steps to differentiate themselves from competitors if they hope to avoid commodification and fee compression. Originality/value: The study is the first to the authors' knowledge to examine real estate executives' perspectives about the roles property managers play in the value creation process, as well as their views about whether property managers have the skills and autonomy required to make value accretive decisions.